PREFERENSI PELAKU INDUSTRI TEMPE TERHADAP KUALITAS BAHAN BAKU KEDELAI DI KECAMATAN SEMARANG SELATAN, KOTA SEMARANG - Diana Mayasari; Titik Ekowati; Migie Handayani (Universitas Galuh, 2023)
Soybean is the main source of vegetable protein for the people of Indonesia. Indonesian soybean consumption is mostly used for tempe production. Soybean processed foods such as tempe are produced by home industries. In producing tempe, the quality of soybean raw materials needs to be considered. Good and bad quality soybean raw materials can affect the quality of the tempe produced. Tempe producers should determine what kind of soybean quality is suitable for use according to the needs and desires of each individual. This study aims to analyze the preferences of the tempe producers on the quality of soybean raw materials, and identify the quality attributes of soybeans based on the order of importance of the tempe producers in South Semarang Sub-District, Semarang City. The method used in this study is a census with a total of 51 respondents in the home industry. Data were collected through observation and interviews using a questionnaire. The research data were analyzed using conjoint analysis. The results showed that the tempe producers' preferences for the quality of soybean raw materials were big seed size, yellow seed color, round seed shape, similar size, and high swellability. Soybean quality attributes based on the order of importance of the tempe producers are seed size, seed swellability, seed color, seed size similarity, and seed shape. Hypothesis testing also shows that there is a strong correlation between the estimated preference and the actual preference.